Autonomic responses to tooth clenching in migraineurs—augmented trigeminocardiac reflex?. (3rd August 2018) - Zaproudina, Nina; Lipponen, Jukka A.; Tarvainen, Mika P.; Vierola, Anu; Rissanen, Saara M.; Karjalainen, Pasi A.; Närhi, Matti
Summary: Background: Systemic autonomic changes are well known in migraineurs. Also, masticatory disorders are reported to be associated with migraine. However, if those phenomena are interrelated, and how, is unclear. Moreover, the knowledge on the autonomic responses to masticatory stimuli in migraineurs is limited. Objective: To investigate tooth clenching‐related cardiac autonomic regulation in migraineurs. Methods: We compared maximal tooth clenching‐induced systemic autonomic responses, indicated by heart rate variability and blood pressure changes, in headache‐free migraineurs (n = 17) and control subjects (n = 22). Results: Levels of high‐frequency power, reflecting vagal activity, were lower in migraineurs at baseline but increased after tooth clenching whereas in controls they returned to baseline ( P  < 0.05, mixed model analysis). In multivariate regression model, the presence of migraine predicted the baseline levels of low‐ and high‐frequency power and sympathovagal balance, and the post‐test increase in high‐frequency power, with the attack frequency and side of headache as the modifiers of the measured changes in migraineurs. The painful signs of temporomandibular disorders, found in clinical oral examination, enhanced both maximal changes in RR intervals and post‐test vagal responses to tooth clenching only in migraineurs. Conclusion: The enhanced post‐clenching vagal activation may represent a marker of the augmented trigeminocardiac reflex to stimulation of trigeminal area, sensitised in migraineurs. Our results support an involvement of autonomic mechanisms in migraine pathophysiology and are interesting in terms of interactions between migraine and masticatory disorders, elucidating one potential way how masticatory disorders may aggravate migraine.